Formation of General Agreement on Tariffs and Trade and World Trade Organization (International relations and international law Journal, 2016)
This article describes the evolution and formation of the GATT / WTO as a universal international trade organization. The authors presents different points of view on the steps of the regulation of international trade. Particularly, special attention is paid to the disclosure mechanisms of Uruguay, Kennedy Dillonskogo, Tokyo and the new Uruguay Round of multilateral trade negotiations, which has as the main objectives the establishment of an orderly system for regulating world trade through the development of tariff and non-tariff measures and anti-dumping and framework agreements. The authors noted that the negotiation was associated with difficulties, which firstly associated with primarily officialposition of the U.S. on the principles of conducting foreign trade with other countries based on common rules of nondiscrimination and the free market. The problems of world trade, which were laid in the early stages of the organization were analyzed.
Keywords: GATT; the General Agreement on Tariffs and Trade; WTO; World Trade Organization; the IMF; the International Monetary Fund; the UN; the United Nations; ITO -International Trade Organization; E-commerce